Sustainability Reporting dan Return Saham di Perusahaan Terindeks LQ45 - Weda, Nyoman; Sudana, I Putu (E-Jurnal Akuntansi; Vol 31 No 6 (2021), 2021)
In recent years, investors have put pressure on companies to disclose more sustainability information. The purpose of this study was to determine the effect of the intensity of disclosure in sustainability reporting on stock returns. This research was conducted on companies with shares listed in the LQ45 index on the IDX. The number of samples taken was 17 companies, with a purposive sampling method. Data collection was carried out by documentation study. The analysis technique used is the panel data regression analysis technique. The results showed that the intensity of disclosure in sustainability reporting has no effect on stock returns. The high intensity of disclosure does not necessarily attract investors to invest and increase the company's stock return. Keywords: Sustainability Reporting;  Profitability; Company Size;   Stock Return.